Pharmacogenetic insights into depression and antidepressant response: does sex matter? - Pitychoutis, P M; Zisaki, A; Dalla, C; Papadopoulou-Daifoti, Z. (Curr Pharm Des, 2010)
It is known that the frequency of men and women suffering from stress-related neuropsychiatric disorders is all but proportionally distributed. Notably, women are far more susceptible than men to the precipitation of depressive symptomatology. Some studies attribute this sex-specific vulnerability to the pronounced genetic predisposition that women may present towards the development of depressive disorders. Furthermore, clinical evidence support the notion that antidepressant response is also characterized by sex-specific manifestations; women may have a better outcome when treated with selective serotonin re-uptake inhibitors, in comparison to tricyclic antidepressants. Despite the fact that the contribution of the "genome" remains elusive when it comes to major depression, intriguing evidence has recently emerged pointing to sexually dimorphic influences of certain polymorphisms in genes related to the pathophysiology of major depression and antidepressant response, such as the serotonin transporter (5-HTT), serotonin 1A (5HT1A) receptor, monoamine oxidase A (MAO-A) and others. Given that the ultimate goal of pharmacogenetics is to provide "tailor-made" pharmacotherapies based on the genetic makeup of an individual, the factor of "sex" needs to be carefully addressed in disorders that are characterized by sex specific manifestations. The aim of the present article is to highlight the impact of sex in depression and in antidepressant pharmacoresponse by providing intriguing insights from the field of pharmacogenetics.
Keywords: Adolescent; Adult; Aged; Antidepressive Agents; Child; Depressive Disorder; Drug Therapy; Female; Humans; Male; Middle Aged; Mutation; Nerve Tissue Proteins; Pharmacogenetics; Pharmacokinetics; Polymorphism, Genetic; Precision Medicine; Sex Factors; Treatment Outcome; Young Adult